Regulatory Effect of Government Quality Award on the Relationship between Quality Management Activities and Enterprise Quality Innovation Performance and Analysis of Employees’ Psychological Demand in Quality Management Activities - Zhixin Wu, Liufang Yi (Forest Chemicals Review)
The Since 2000, Chinese governments at all levels have successively carried out the evaluation of government quality awards and achieved certain results. However, how to prove the impact of various quality management activities adopted by government enterprises on enterprise performance, especially quality innovation performance, and how to explore the action mechanism of Government Quality Award activities on quality innovation performance, as well as the psychological demand of employees in quality management activities, will be the main problems of this study. This paper examines the regulatory effect of quality management activities and enterprise quality innovation through the institutional factor of government quality award. This study takes the enterprises from Zhejiang province that have won the county, city, district or provincial government quality award as the research object, including more than 80 enterprises in Hangzhou, Wenzhou, Taizhou and Lishui. This study uses statistical analysis, takes more than 80 enterprises as effective samples, and utilizes SPSS13 statistical software further verifies the theoretical conception of this study quantitatively. This study studies the changes of quality management activities, innovation performance and employees’ psychological demand, and tests the relationship between various factors in various quality management activities and enterprise quality innovation performance and employees’ psychological demand. In this study, the Government Quality Award activities at all levels have a significant effect on the innovation performance of enterprises and play a boosting role. This shows that various quality management activities adopted by the government are of great significance to the improvement of enterprise performance as long as they are implemented in place and provided with accurate services; According to the research conclusion, combined with the shortcomings of the existing research, this paper puts forward the future research direction and the corresponding management enlightenment, which has certain theoretical and practical significance; Under the social and cultural background of our country, the psychological demand of employees is introduced as a regulating variable to study the relationship between various quality management activities and innovation performance.